El apoyo familiar y la resiliencia como un factor importante en el proceso que enfrentan las mujeres con cáncer que hacen parte de la fundación mujeres de loto en el municipio de Soacha Cundinamarca durante el año 2020 (2020)
After hard work to find relevant information to guide this project, there is an interest in developing research focused on understanding family support and resilience in the process faced by women with cancer. During its development, significant contributions and experiences are integrated at a personal and academic level. The following research is entitled: "Family support and resilience as an important factor in the process faced by women with cancer who are part of the Fundación Mujeres de Loto in the municipality of Soacha Cundinamarca during the year 2020." Information is collected through a semi-structured interview, in which a series of questions are developed to 5 women, two of them recovered and who have been part of the foundation since its inception. On the other hand, for the development of this work, the authors Elssy Bonilla and Penélope Rodríguez are taken as a methodological reference under the process that they present in their book "Beyond the Dilemma of Methods" where they propose 6 phases to carry out a project research: exploration of the situation, research problem, design, sample configuration, collection of information and finally the organization, analysis and interpretation of the data. To support this project, we start from the postulates of the comprehensive interpretive paradigm, whose purpose, according to Lincoln and Guba (1985), is to recognize a reality from the context and interpret it from it. A descriptive research level is presented which, according to Sampieri, intends to specify important properties and characteristics of any phenomenon that is analyzed. Describe trends in a group or population. Finally, the model from which we work is social constructionism with a qualitative approach, which, as proposed by the authors, involves a deep analysis and interpretation of the data to respond to what is intended to investigate. The interest in carrying out this research is based on the intention to understand family support and resilience as an important factor in the process faced by these women. It is a necessity for the Mujeres de Loto Foundation, whose abbreviation is FML, to know and understand the importance of family relationships from a perspective of family support and resilience, thus allowing to identify if they contribute to their process in a positive way. Finally, as a contribution to the University, the foundation and mainly to the collaborating women in this process, the research group develops a proposal for a future intervention that is oriented from the suggestions given by the foundation and some contributions obtained through the interviews carried out with administrative personnel and women who attend the foundation.